CHEMICAL AND ORGANOLEPTIC CHARACTERISTICS OF CHICKEN NUGGET BASED ON COMPOSITE FLOUR FROM MOCAF, BROWN RICE AND CORN STARCH - Lia Hairunnissa; Arni Komala Sari; Irawan Satrio Jati; Ila Maratush Shalihah; Sarah Dhia Akifah; Azizah Nur Izzati; Nia Ariani Putri; Zulfatun Najah (University of Sultan Ageng Tirtayasa, 2021)
One of the foods favored by the public is nugget which is a fast food group with meat-based ingredients. In this study, mocaf, brown rice flour and corn starch were used as an alternative fillers to wheat flour as a means of reducing dependence on wheat flour as an imported product and increasing the nutritional content of nuggets. The purpose of this study was to determine the effect of variations in the formulation of ingredients on the organoleptic characteristics and chemical content of the nuggets that were most favored by the panelists. This research began with the nugget formulation, followed by organoleptic testing and chemical characterization of the nugget formula that was preferred by the panelists. The average results of the affection test showed that nugget B was preferred to nugget A, which used less, with the ingredient formula having a ratio of mocaf, brown rice flour and cornstarch, namely 4:1:3 (60g:15g:45g). The selected nugget formula contains water as much as 57.553%, fat content 1.055%, ash content 1.955%, protein 29.195%, crude fiber 16.064%, and carbohydrates other than fiber 10.205%. By not using wheat flour as the main ingredient, these nuggets can be regarded as an alternative food that is low in gluten and high in fiber because of the content in carrots, brown rice flour, and mocaf.